Formation of Students' Socio-Emotional Character During Traditional Sports Week in Elementary Schools - Rahman , Trio Deswa; Dinangsit, Dinar; Safari, Indra (Universitas Majalengka, 2025)
This research is motivated by the declining interest of the younger generation in traditional sports amid the digital era, which is weakening national character. In fact, traditional sports not only serve as physical activities but also embody noble cultural values that can shape students' social and emotional character. The purpose of this study is to describe how Traditional Sports Week activities can strengthen students' social and emotional character in Public Elementary Schools in Bangkunat District, Pesisir Barat Regency, Lampung. This study uses a qualitative approach, focusing on three main variables: social-emotional character, Traditional Sports Week activities, and student participation. The research subjects included students, teachers, and parents involved in the activities. Data were collected through observation, interviews, and documentation during the implementation of Traditional Sports Week, which takes place once a week. The results of the study are expected to show that Traditional Sports Week activities can be an effective means of fostering social values such as cooperation, empathy, and sportsmanship, as well as strengthening students' emotional abilities to manage feelings, respect others, and adapt to the environment. The findings of this study are expected to make theoretical contributions to the development of local wisdom-based character education, as well as serve as a practical reference for schools in developing relevant co-curricular activities to shape students' social-emotional character in the modern era.